The Adlay cereal in rations for growing-finishing pigs - Gomes, Paulo Cezar; Ferreira, Aloizio Soares; Fialho, Elias Tadeu; Barbosa, Hacy Pinto (Pesquisa Agropecuaria Brasileira, 2014)
A trial was carried out as the Concórdia Swine Experimental Station-SC, with the purpose of testing the cereal Adlay (Croix lacrima jobi) in rations for growing-finishing pigs and of verifying its biological value from digestibility trial. Forty-eight crossbreed pigs (Landrace x Large white) were used, being 24 barrows and 24 gilts, with an initial average weight of 28 kg. A complete randomized design was used, comprising four treatments (A-0.0; B-1.0; C-20.0 and D-30.0% Adlay in the ration) and six replications. The average daily gain (g), daily feed intake (g) and feed efficiency from 28 to 9O kg live weight were: 712, 2291, 3.22; 662, 2147, 3.25; 642, 2131, 3.32; 650, 2312, 3.56 for treatments A, B, C and D, respectively. No significant difference in daily gain, daily feed intake and carcass characteristics was presented among treatments. Pigs fed with 30.0% Adlay rations presented the lowest feed efficiency (P<0.05). These value obtained for digestible dry matter and digestible energy for the Adlay were lower than for corn. Treatments receiving 0.0; 10.0 and 20.0 percent Adlay did not show significant difference. The carcass characteristics and performance were not affected when Adtay was present up to 20% in the ration. Ten percent "Adlay" present greater returns than 0.0; 20.0 and 30.0 percent (Cr 4.59; 34.72 and 158.62, respectively).